Estudo da adsorção em fase líquida do vermelho congo sobre adsorventes micro e mesoporosos - Ribeiro, Thaís Regina Silva (2019)
The adsorption of the congo red dye on the NaY zeolite and the MCM-41 mesoporous material with and without lanthanum was investigated in aqueous solution in a batch system with the objective of studying the kinetics and the adsorption equilibrium and the application potential of these materials in the treatment of textile effluents. To obtain the mesoporous material, the synthesis was carried out by hydrothermal method followed by calcination, NaY zeolite was commercially obtained, LaMCM-41 and LaNaY materials were obtained by mechanical mixing and impregnation, respectively. The adsorbent materials were characterized by X-ray diffractometry (XRD), nitrogen adsorption at 77 K and thermal analysis via TG / DTG. The XRD of the microporous (NaY) and mesoporous materials (MCM-41) showed that they present the main peaks related to NaY and MCM-41 structures and also that the incorporation of lanthanum into the structure of the materials was possible without significant change the crystallinity and degree of ordering thereof. The adsorption and desorption characterization of N2 at 77 K showed that the textural properties of NaY and MCM-41 are typically observed and that after the insertion of lanthanum, the microporous material showed a greater change in these properties compared to the mesoporous ones. The adsorption assays of the red dye congo showed that the LaMCM-41 adsorbent showed a higher removal efficiency of this dye in comparison with the microporous material containing lanthanum (LaNaY), in all time interval studied. These results are directly correlated with the largest total area, volume and pore diameter of LaMCM-41 in relation to LaNaY. The systems with lower concentrations of the dye (10 mg L-1 and 20 mg L-1) achieved the balance between 40 and 90 minutes, whereas for the system with the highest dye concentration (30 mgL-1) the balance is reached between 5 and 10 minutes. In order to study adsorption kinetics, a pseudo-first-order model and the Chi-square test were applied to the experimental data. To study the adsorption equilibrium the experimental data were adjusted using the Langmuir and Freundlich models. The Langmuir model was better fitted to the experimental data for the mesoporous adsorbents, however the system with microporous adsorbents presented better correlation with the Freundlich model.